The clash of economic ideas : the great policy debates and experiments of the last hundred years - White, Lawrence H. (New York : Cambridge University Press, 2012)
"The Clash of Economic Ideas interweaves the economic history of the last hundred years with the history of economic doctrines to understand how contrasting economic ideas have originated and developed over time to take their present forms. It traces the connections running from historical events to debates among economists, and from the ideas of academic writers to major experiments in economic policy. The treatment offers fresh perspectives on laissez faire, socialism and fascism; the Roaring Twenties, business cycle theories and the Great Depression; Institutionalism and the New Deal; the Keynesian Revolution; and war, nationalization and central planning. After 1945, the work explores the postwar revival of invisible-hand ideas; economic development and growth, with special attention to contrasting policies and thought in Germany and India; the gold standard, the interwar gold-exchange standard, the postwar Bretton Woods system and the Great Inflation; public goods and public choice; free trade versus protectionism; and finally fiscal policy and public debt"--
Includes bibliographical references and index.
Keywords: Economics -- History -- 20th century; Economics -- History -- 21st century